Annotation of greeting, introduction, and leavetaking in dialogues - Spillane, Brendan; Wade, Vincent; Campbell, Nick; Gilmartin, Emer; O'Reilly, Maria; Saam, Christian; Su, Ketong; Levacher, Killian; Cerrato, Loredana; Cowan, Benjamin R.; Clark, Leigh; Calvo, Arturo (My University, 2017)
Dialogue act annotation aids understanding of interaction structure, and also in the design of artificial dialogue. While many dialogues can be described as task-based or instrumental, others are more interactional. These categories are not mutually exclusive; many service encounters include social talk. Much research on dialogue and particularly on description of dialogue acts for use in dialogue systems has focused on task-based dialogue. However, attention has been focusing on social aspects of spoken and text interaction, particularly in light of newer systems designed for domains such as companionship. In this paper we briefly describe social or casual talk, review how current dialogue annotation schemes, and particularly the ISO standard 24617-2 “Semantic annotation framework, Part 2: Dialogue acts”, treat non-task elements of dialogue. We describe the collection and annotation using the ISO standard of a corpus of 193 text dialogues, report on an analysis of dialogue acts used in greeting, introductions and leave-taking, and propose new dialogue acts to provide coverage of these fundamental conversational sequences.
PUBLISHED
Keywords: Dialog acts; Interactional talk; Digital Engagement; Annotation; Dialog Corpus; Greeting and Leave-taking; Social Dialogue; Communication